Respon Pertumbuhan Akar Tanaman Sengon (Paraserianthes falcataria) terhadap Kepadatan dan Kandungan Air Tanah Podsolik Merah Kuning - Omo Rusdiana; Yahya Fakuara; Cecep Kusmana; Yayat Hidayat (Jurnal Manajemen Hutan Tropika, 2000)
The purpose of this experiment was to investigate the influence of soil compaction and water content on root development of 6 month old sengon seedling. The experiment was arranged 3 x 3 factorial experiment within a complete randomized design and 3 replications. The factor number one was soil compaction and factor number two was soil water content. The soil compaction factor consists of 3 levels, which are 1,5 g/cm3 (A1), 1,2 g/cm3 (A2), and 0,9 g/cm3 (A3) respectively, while the soil water content also consists of 3 levels, which are 60,41 % (B1), 49,64% (B2), and 42,86 % (B3) for each level. The parameters were counted which are root number, diameter, root length, biomass, surface area, and root length density. The result was that soil compaction treatment has a significant influence to root number, root length, biomass, surface area, and root length density. On the other hand the soil water content treatment on pF 2,54 until 3,5 and interaction soil compaction and water content have no influence to root number, diameter, root length, biomass, surface area, and root length density. Root number, diameter, length, biomass, surface area and root length density were increased accordingly to the age of the seedling, but the increasing of soil compaction has decreased to the number, length, root length, biomass, surface area and root length density. The secondary root was found more larger than the primary and the tertiary root in term of the root length, surface area and root length density.